Taxonomic changes in Oenothera sections Gaura and Calylophus (Onagraceae) - Warren Wagner; Kyra Krakos; Peter C. Hoch (PhytoKeys, 2013)
The long-recognized genus Gaura was shown recently to be deeply nested within one of two major clades of Oenothera. New molecular data indicate further taxonomic changes are necessary in Oenothera sect. Gaura. We make these changes here, including three new combinations, in advance of the Onagraceae treatment for the Flora of North America. The new phylogenetic studies show that several pairs of taxa treated as subspecies in the most recent revision by Raven and Gregory (1972) had independent origins within sect. Gaura, and are here elevated to species level (Oenothera nealleyi for Gaura suffulta subsp. nealleyi; Oenothera dodgeniana for Gaura neomexicana subsp. neomexicana; and Oenothera podocarpa for Gaura hexandra subsp. gracilis). Also, a nomenclatural problem in Oenothera sect. Calylophus is corrected by adopting the name Oenothera capillifolia Scheele for the species known previously, and nomenclaturally correct, as Calylophus berlandieri Spach. This problem necessitates a new combination Oenothera capillifolia subsp. berlandieri.